Methodology and methods of Linguistics: case study - Yefremova, Nataliia; Boichuk, Valentina; Rys, Larysa (Дрогобицький державний педагогічний університет імені Івана Франка, 2025)
The article highlights case study research as a vital and evolving method in linguistics, offering insights into the complex and contextualized nature of language phenomena. Despite inherent limitations regarding generalizability, case studies provide unparalleled depth of understanding that contributes significantly to theoretical development and practical applications in various fields of linguistics. It is shown that in linguistic research, case studies typically focus on individual language learners, teachers, speakers, communities of practice, or specific linguistic situations. The survey shows main typologies of case study research, the understanding of which is crucial for designing a rigorous and purposeful linguistic inquiry. Robert Stake’s intrinsic, instrumental, and collective cases, and Robert Yin’s descriptive, exploratory, and explanatory case studies, highlight the method’s flexibility and strategic alignment with diverse research objectives. Qualitative approach and naturalistic inquiry serve as philosophical underpinnings, underlying basic methodological principles of case study research in linguistics, these being boundedness and singularity, in-depth investigation, multiple perspectives, contextual emphasis, and inductive reasoning. The article dwells on the process of case study research in linguistics that encompasses careful research design, diverse data collection techniques, and rigorous qualitative data analysis. The analysis typically progresses through several stages: describing experience, describing meaning, focus of the analysis. Thematic analysis, discourse analysis, narrative analysis, and grounded theory are common qualitative data analysis methods particularly suited for linguistic case studies. The future of case study research in linguistics depends on researchers’ ability to balance methodological innovation with established principles of rigorous qualitative inquiry, ensuring that this approach continues to generate meaningful insights into the complex world of human linguistic behavior.

У статті висвітлено особливості застосування кейс-методу як надзвичайно важливого методологічного інструментарію лінгвістичних досліджень, який пропонує унікальне розуміння складної, контекстуалізованої природи мовних явищ. Попри певні обмеження щодо процесу узагальнення, кейс-метод забезпечує достатню глибину розуміння явиищ та процесів, що значною мірою сприяє його теоретичному розвитку та практичному застосуванню в різних галузях лінгвістики. У лінгвістичних дослідженнях кейс-метод зазвичай застосовується для аналізу конкретних ситуацій чи проблем, пов’язаних з окремими особами, які вивчають мову, викладачами, носіями мови, або конкретнми лінгводидактичними чи мовними/мовленнєвими/комунікативними ситуаціями. Пропонований огляд знайомить з основними типологіями кейс-методу, розуміння яких є вирішальним для розробки дизайну лінгвістичного дослідження. Внутрішні, інструментальні та колективні кейси Р. Стейка, а також описові, дослідницькі та пояснювальні кейси Р. Іня підкреслюють гнучкість методу та його стратегічну відповідність різноманітним дослідницьким цілям. Якісний та натуралістичний підходи слугують філософськими підвалинами основних методологічних принципів дослідження кейсів у лінгвістиці. Ними є обмеженість та сингулярність, поглиблене дослідження, множинні перспективи, контекстуальність, індуктивне мислення. У статті розглядається процес застосування кейс-методу в лінгвістиці, який охоплює ретельне планування дослідження, різноманітні методи збору даних та їхній якісний аналіз. Цей процес зазвичай проходить декілька етапів: опис конкретної ситуації, опис значення, власне аналіз. Тематичний аналіз, дискурс-аналіз, наративний аналіз та обґрунтована теорія є методами якісного аналізу даних, суголосими з ситуаційними дослідженнями в лінгвістиці. Майбутнє кейс-методу в лінгвістиці залежить від здатності дослідників віднайти рівновагу між методологічними інноваціями та усталеними принципами якісного дослідження, гарантуючи, що цей підхід продовжуватиме сприяти розумінню мовної/мовленнєвої поведінки людини.
Keywords: methodology; methodological principles; method; case study; Linguistics; data analysis; 11.112.2’42:378.147.091.33